The Effect of Shading Devices in Rising Damp Phenomenon of Historical Buildings - J. M. P. Q. Delgado (2012)
Rising damp is the upward movement of ground water through a permeable masonry wall. The water rises through the pores in the masonry via a process called capillarity. Capillarity is a process whereby water molecules are electrochemically attracted to mineral surfaces, enabling water to move vertically through pores of a certain size despite the counteractive force of gravity. The great majority of the papers presented in literature only analyse the external shading effect on building energy conservation; and this work intends to present a preliminary analyse of the effect of shadows in rising damp phenomenon. We present an exhaustive numerical analyse of the shading effect on historical buildings. The shading effect due vertical nearby obstacles, as trees, or horizontal obstacles is causing mould and or rising damp phenomenon in historical buildings, as a result of moisture increasing. The results show the importance of obstacles (shading effect), as trees, nearby the old constructions in the rising damp, namely in the height of steady-state capillary rise and in the drying process.